A study of college students' intention to use metaverse technology for basketball learning based on UTAUT2. Issue 9 (September 2022) - Yang, Fangfang; Ren, Longfei; Gu, Chao
Abstract: Recent advancements in virtual reality technology have attracted increasing attention from enterprises and scholars, and many new related products have been launched. Due to the current COVID-19 epidemic, the non-face-to-face teaching environment will seriously affect students' basketball learning. We therefore combined basketball learning with metaverse technology, discussed basketball teaching in a virtual reality environment, and examined the influencing factors of college students' intentions to use metaverse technology. In the light of UTAUT2, a new research model was proposed, and quantitative research was carried out. The results of a survey of 1074 valid samples revealed that habits and attitudes are crucial factors in the success of basketball learning using a metaverse. The findings also indicate that grade and gender are moderator variables. Abstract : Metaverse; Basketball teaching; Virtual space; UTAUT2.